(untitled) (Research, Society and Development, 2020)
Retinitis Pigmentosa (RP) is a retinal disease characterized by varied genetic mutations in its pathogenesis, it belongs to a group of progressive retinal dystrophies genetically inherited and results from the death of the retinal pigment epithelium and photoreceptors, being characterized by rod degeneration, followed by by the cones. In order to contribute to a greater understanding of this topic, given its socioeconomic impacts and the quality of life of patients, an integrative literature review was carried out with a total of 22 articles. After analysis, it was observed that the disease can be divided into typical, more common, and atypical, according to its pathophysiology, or syndromic and non-syndromic, based on the set of clinical manifestations. In addition, symptoms can begin in childhood or adulthood, with unpredictable progression, with visual loss being classically symmetrical and bilateral, initially peripheral, progressing until only part of the central visual field remains. Regarding the ophthalmic examination, the main findings were deposits of peripherally pigmented bone spikes, associated with atrophy and / or dystrophy of the retinal pigment epithelium, attenuation of the retinal vessels, pallor of the optic nerve and relatively spared macula. Complementary tests include central and peripheral visual field mapping, electroretinography, optical coherence tomography, and fundus autofluorescence. The diagnosis of PR is related to the appearance of depressive symptoms, and its management was characterized by requiring a multidisciplinary approach, so that the available treatment is supportive, with auxiliary measures for low vision, tests and genetic counseling and treatment of conditions associated, with no curative therapy.